Delamination study on glass/carbon hybrid composite laminates for structural applications. (2023) - Murugan, R.; Sandeep, S.; Ragulraj, R.; Saravanakumar, S.S.; Gnanakumar, G.
Abstract: Fiber reinforced polymer (FRP) composite laminates are widely used in engineering applications covering from aerospace to household appliances due to their high strength-to-weight ratio. In all these applications, the use of mechanical fasteners in assembling process necessitates the drilling of composite panels. Drilling the composite panels, on the other hand, poses a serious threat to the quality of the holes and thereby joint strength. The goal of this research is to improve the quality of holes drilled in glass/carbon hybrid composite laminates, which are widely used in engineering. The hand layup method was used to fabricate all of the preferred laminates. A vertical machining centre was used to drill holes in composite laminates (AMS MCV-350). The L9 orthogonal array was employed to obtain the best results for three preferred drilling process control parameters: drill bit diameter, spindle speed and feed rate. For the delamination analysis of glass/carbon hybrid composite laminates, the equivalent delamination factor (Fed ) is used. The equivalent delamination factor of each drilled hole was measured using the digital image analysis method. Based on the experimentally determined values of the equivalent delamination factor, an effective layering arrangement was also proposed in order to achieve a quality hole with the least amount of delamination in glass/carbon hybrid composite laminates. An analysis of variance (ANOVA) was also performed on the experimental results to find the best process parameters for drilling the glass/carbon hybrid laminates with minimum delamination. The ANOVA results revealed that drill bit diameter has a greater impact on delamination than spindle speed and feed rate when drilling glass/carbon hybrid composite laminates.